HUBUNGAN ANTARA AKTIVITAS FISIK DENGAN LINGKAR PINGGANG PADA SISWA OBES SENTRAL - Ra Pati Tiala, Maria Elisabeth Adeline; Tanudjaja, George N.; Kalangi, Sonny J. R. (Universitas Sam Ratulangi, 2013)
Abstract: Background. Obesity has become a worldwide problem. Obesity is caused by energy intake that is greater than energy expenditure. Physical activity is one of energy expenditure. Measuring waist circumference is a method that frequently done to determine obesity. Physical activity can reduce waist circumference regarding decreased body fat percentage especially in visceral fat. Objective. This research was aimed to know the relationship between physical activity and waist circumference in central obese students. Method. An observational method with cross sectional design research was done in November and December 2012 in Saint Ignatius Catholic High School Malalayang Manado. Global Physical Activity Questionnaire (GPAQ) is used in measuring physical activity. Waist circumference was measured with OneMed tape. The analysis used Spearman correlation test. Result. The waist circumferences of 61 respondents were in central obesity. The lowest value of Metabolic Energy Turnover (MET) was 900 MET-minutes/week and the highest was 2,900 MET-minutes/week. In 10 men respondents, the smallest waist circumference was 90.2 cm and the biggest was 110.5 cm. In 51 women respondents, the smallest waist circumference was 80.3 cm and the biggest was 99.0 cm. Conclusion. There was no significant relationship between physical activity and waist circumference (p=0,077). Keyword: physical activity, waist cifcumference, obesity, central obese.Â Â Abstrak: Latar Belakang. Obesitas menjadi masalah di seluruh dunia. Obesitas disebabkan karena masukan energi melebihi penggunaan energi. Aktivitas fisik ialah salah satu penggunaan energi. Cara yang sering digunakan untuk menentukan obesitas yaitu dengan mengukur lingkar pinggang. Aktivitas fisik mampu menurunkan ukuran lingkar pinggang karena berkaitan dengan penurunan persentase lemak tubuh terutama lemak viseral. Tujuan. Penelitian ini bertujuan untuk mengetahui hubungan antara aktivitas fisik dengan lingkar pinggang pada siswa obes sentral. Metode. Penelitian observasional dengan desain cross sectional dilaksanakan pada Bulan November sampai Desember 2012 di SMA Katolik Santo Ignatius Malalayang Manado. Pengukuran aktivitas fisik menggunakan kuesioner Global Physical Activity Questionnaire (GPAQ). Lingkar pinggang diukur dengan pita ukur OneMed. Analisis menggunakan uji korelasi Spearman. Hasil. Sebanyak 61 responden mempunyai lingkar pinggang dengan obes sentral. Nilai Metabolic Energy Turnover (MET) terendah ialah 900 MET-menit/minggu dan tertinggi ialah 2.900 MET-menit/minggu. Pada 10 responden laki-laki, lingkar pinggang paling kecil yaitu 90,2 cm dan paling besar 110,5 cm. Pada 51 responden perempuan, lingkar pinggang paling kecil ialah 80,3 cm dan paling besar ialah 99,0 cm. Simpulan. Tidak terdapat hubungan yang signifikan antara aktivitas fisik dengan lingkar pinggang (p=0,077). Kata kunci: aktivitas fisik, lingkar pinggang, obesitas, obes sentral.